Concurrent Hiatal Hernia and Megaesophagus Secondary to a Nasopharyngeal Polyp in a 6-month-old Cat - Kim, Kihoon (Acta Scientiae Veterinariae, 2021)
Background: Nasopharyngeal polyps are benign and inflammatory masses assumed to arise from the middle ear or the eustachian tube with extension into the pharynx. The most common clinical signs associated with nasopharyngeal polyps include respiratory stertor, dyspnea, and otic discharge Neurological signs, including head tilt, facial nerve paralysis, and ataxia, might indicate concurrent involvement of the middle or inner ear. The objective of the current study is to describe a case of a feline nasopharyngeal polyp with a concurrent hiatal hernia and megaesophagus, both spontaneously resolved after removal of the polyp. Case: A 6-month-old, intact, female, domestic shorthair cat presented for evaluation of lethargy, anorexia, and upper respiratory signs, such as stridor, stertor, and dyspnea. A thoracic radiography revealed esophageal dilation caudal to the cardiac silhouette, suggestive of megaesophagus with gaseous filtration. An esophagram confirmed a hiatal hernia and megaesophagus. Computed tomography revealed a nasopharyngeal mass adjacent to the soft palate and a soft-tissue density in the right tympanic bulla. A tentative diagnosis of a nasopharyngeal polyp was made. After the ventral bulla osteotomy, the nasopharyngeal mass was removed by a gentle traction avulsion technique. Six days after the surgery, hiatal hernia and megaesophagus were spontaneously resolved. Based on histopathologic exam, the mass was found to be an inflammatory nasopharyngeal polyp. Two months after surgery, the owner reported that the patient’s condition had returned to baseline with a good appetite, and the thoracic radiography was within normal limit. Six months after the surgery, the owner reported the patient was completely recovered from the upper airway obstruction signs. Discussion: For successful treatment of a nasopharyngeal polyp, traction avulsion of the polyp with or without a ventral bulla osteotomy is recommended. However, in patients with otitis media, a ventral bulla osteotomy followed by traction avulsion of the polyp is recommended in order to reduce the rate of polyp recurrence. Common clinical signs of a nasopharyngeal polyp are stertor, stridor, dyspnea, dysphagia, and open-mouth breathing, which are identified in a chronic upper airway obstruction. A hiatal hernia secondary to a nasopharyngeal polyp has not been reported so far. However, a relationship between chronic upper airway obstruction and hiatal hernias has been proposed previously. Moreover, hiatal hernia resolved spontaneously after removal of the nasopharyngeal polyp suggests that the occurrence of the hiatal hernia was secondary to the nasopharyngeal polyp. In addition to the hiatal hernia, megaesophagus was also identified in the present case. Megaesophagus secondary to a chronic upper airway obstruction from a nasopharyngeal obstruction has been reported. However, megaesophagus is also thought to occur secondary to hiatal hernias. Therefore, in the current study, it is unclear whether the megaesophagus was solely a result of the obstructive nature of the nasopharyngeal polyp or a combination of the hiatal hernia and the nasopharyngeal polyp. In conclusion, any cat with clinical signs of an upper airway obstruction and a concurrent hiatal hernia and megaesophagus should be thoroughly investigated for a nasopharyngeal polyp, as well as other gastrointestinal and systemic causes. Furthermore, this case suggests that the prognosis for a concurrent hiatal hernia and megaesophagus is good in cats if the nasopharyngeal polyp is properly removed. Keywords: cat, hiatal hernia, megaesophagus, nasopharyngeal polyp